The conservation and protection of the black rhinoceros Diceros bicomis in Zimbabwe - G.H. Tatham; R.D. Taylor (Koedoe: African Protected Area Conservation and Science, 1989)
Selected Papers from the Rhinoceros Conservation Workshop, Skukuza, Kruger National Park,31 August – 4 September 1988 The demise of black rhinoceros populations in Africa is alarming and the overriding cause for the decline is illicit poaching for horn. In 1987 Zimbabwe hosted the largest contiguous population of 500 animals in the Zambezi Valley while the country's overall population is now estimated to be nearly 2 000 individuals. A strategy to conserve and protect the black rhinoceros Diceros bicomis in Zimbabwe requires four dimensions, each dependent directly or indirectly on the other, if success is to be achieved. It includes a positive reaction by the Department of National Parks and Wild Life Management, a national reaction by the government totally committed to the protection of the species, an international reaction requiring support for the stand that Zimbabwe is taking and, finally, a system of intelligence gathering which assists the different authorities in the overall conservation strategy which is being implemented.